The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/14767050400018056
|View full text |Cite
|
Sign up to set email alerts
|

Random urinary protein-to-creatinine ratio for prediction of significant proteinuria in women with preeclampsia

Abstract: In hospitalized preeclamptic patients, the random urinary protein-to-creatinine ratio at a cutoff of > or = 0.25 revealed a highly accurate prediction of significant proteinuria and could be a more practical alternative for assessment of proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
2
25
0
2
Order By: Relevance
“…Several studies have suggested an acceptable correlation between single-voided p:c ratio and 24-h urine protein in pregnant patients. [2][3][4][5][6][7][8][9][10][11] Nevertheless, the results reported may be limited by examining patients with a different underling disease in one study 11 and not having a large enough sample in another one. 10 Some studies were conducted on hospitalised pregnant patients with suspected pre-eclampsia, whose results may not be applicable for outpatient pregnant women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested an acceptable correlation between single-voided p:c ratio and 24-h urine protein in pregnant patients. [2][3][4][5][6][7][8][9][10][11] Nevertheless, the results reported may be limited by examining patients with a different underling disease in one study 11 and not having a large enough sample in another one. 10 Some studies were conducted on hospitalised pregnant patients with suspected pre-eclampsia, whose results may not be applicable for outpatient pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…10 Some studies were conducted on hospitalised pregnant patients with suspected pre-eclampsia, whose results may not be applicable for outpatient pregnant women. 5,6,13 To date only a few studies have measured the sensitivity and the specificity of the test in women suspected of having pre-eclampsia and comparing them with a non-suspect group or all pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, authors such as Yamasmit et al [22] and Jaschevatzky et al [23] have demonstrated a high correlation between 24-hour proteinuria and PCR. Recently, Sethuram et al [27] demonstrated that PCR has a 90% (r 2 = 0.82) correlation with 24-hour proteinuria, with an LH receptor increase of 10.3 when using cutoff values of 0.3 g/mmol (30 mg/mmol) to detect proteinuria values in PE ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Upon studying PCR behavior in the pregnant population, there is greater consensus on the fact that creatinine and protein excretion in urine are reasonably constant throughout the day, when glomerular filtration remains stable, as is the case in PE [22,23,36]. Despite this, there is contrasting evidence regarding the efficacy of such a test to diagnose PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation